Formyl-Peptide Receptor 2/3/Lipoxin A4 Receptor Regulates Neutrophil-Platelet Aggregation and Attenuates Cerebral Inflammation: Impact for Therapy in Cardiovascular Disease. Issue 22 (31st May 2016) - Vital, Shantel A.; Becker, Felix; Holloway, Paul M.; Russell, Janice; Perretti, Mauro; Granger, D. Neil; Gavins, Felicity N.E.
Abstract : Background—: Platelet activation at sites of vascular injury is essential for hemostasis, but it is also a major pathomechanism underlying ischemic injury. Because anti-inflammatory therapies limit thrombosis and antithrombotic therapies reduce vascular inflammation, we tested the therapeutic potential of 2 proresolving endogenous mediators, annexin A1 N-terminal derived peptide (AnxA1Ac2–26 ) and aspirin-triggered lipoxin A4 (15-epi-lipoxin A4 ), on the cerebral microcirculation after ischemia/reperfusion injury. Furthermore, we tested whether the lipoxin A4 receptor formyl-peptide receptor 2/3 (Fpr2/3; ortholog to human FPR2/lipoxin A4 receptor) evoked neuroprotective functions after cerebral ischemia/reperfusion injury. Methods and Results—: Using intravital microscopy, we found that cerebral ischemia/reperfusion injury was accompanied by neutrophil and platelet activation and neutrophil-platelet aggregate formation within cerebral microvessels. Moreover, aspirin-triggered lipoxin A4 activation of neutrophil Fpr2/3 regulated neutrophil-platelet aggregate formation in the brain and inhibited the reactivity of the cerebral microvasculature. The same results were obtained with AnxA1Ac2–26 administration. Blocking Fpr2/lipoxin A4 receptor with the antagonist Boc2 reversed this effect, and treatments were ineffective in Fpr2/3 knockout mice, which displayed an exacerbated disease severity, evidenced by increased infarct area, blood-brain barrier dysfunction, increased neurological score, and elevated levels of cytokines. Furthermore, aspirin treatment significantly reduced cerebral leukocyte recruitment and increased endogenous levels of aspirin-triggered lipoxin A4, effects again mediated by Fpr2/3. Conclusion—: Fpr2/lipoxin A4 receptor is a therapeutic target for initiating endogenous proresolving, anti-inflammatory pathways after cerebral ischemia/reperfusion injury. Abstract : Supplemental Digital Content is available in the text.